Effect of forest fire on tree diversity and regeneration in the forests of Uttarakhand, Western Himalaya, India - Bargali, Himanshu; Bhatt, Dinesh; Sundriyal, Rakesh Chandra; Uniyal, Virendra Pratap; Pandey, Aseesh; Ranjan, Ram (Frontiers in Forests and Global Change, 2023)
The objective of this study was to investigate the impact of forest fires on tree diversity and regeneration in three fire-prone forests of Uttarakhand, India. We used Landsat 5, 7, and 8 satellite imagery to prepare fire frequency maps and the study area was divided into four fire frequency classes. Ten plots were marked in each fire frequency class to assess diversity and regeneration pattern of tree species. A total of 14 tree species belonging to 14 genera and 13 families were sampled during the study period. We found that tree species diversity was higher in areas with low fire frequencies in comparison to the areas with no fire frequency. We also observed that regeneration of tree species varied significantly across all fire frequency classes and forest types, with increasing dominance of certain fire-tolerant species in areas with frequent fires. Of the 33,678 individuals (tree, sapling, and seedling) recorded in all the fire frequency classes, 12,630 were in Sal Forest, 8,033 were in Chir-pine Forest, and 13,015 were in Mixed Forest. The study suggests that if forest fire incidences continue at current levels, the forests could experience a decline in tree diversity consequently. Although forest fire is a natural occurrence in many ecosystems, the increasing frequency and intensity of fires due to human activities such as land-use change and climate change have disrupted the natural fire regime.